Comparative Analysis of Elliptic Curve-Based Cryptographic Approaches for Internet of Things Security - Jean Pierre Ntayagabiri; Jeremie Ndikumagenge; Youssef Bentaleb; Hind El Makhtoum (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The rapid expansion of the Internet of Things (IoT) introduces significant security challenges, given the resource-constrained nature of most IoT devices. To address these challenges, elliptic curve cryptography (ECC) has emerged as a promising solution due to its ability to deliver high levels of security with shorter key lengths, making it highly efficient for devices with limited computational power and memory. This paper focuses on a comparative analysis of three widely used ECC-based cryptographic algorithms: Elliptic Curve Digital Signature Algorithm (ECDSA), Elliptic Curve Integrated Encryption Scheme (ECIES), and Elliptic Curve Diffie-Hellman (ECDH). Through a detailed evaluation of performance metrics such as key generation speed, execution time, and overall efficiency, the study identifies the strengths and limitations of each algorithm in securing IoT environments. The results reveal that ECDH excels in public key generation speed, making it suitable for applications requiring frequent key exchanges. ECDSA demonstrates the fastest overall execution time, providing an efficient option for digital signatures and authentication. Conversely, ECIES, while slower, offers robust encryption capabilities ideal for scenarios demanding enhanced confidentiality. This comparative study highlights the importance of aligning algorithm selection with specific IoT application requirements, balancing factors like security, performance, resource constraints, and operational complexity. The findings underscore the suitability of ECC-based algorithms in addressing the unique challenges of IoT security.